THE STRATEGIC ROLE OF SCHOOL MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN THE ERA OF THE MERDEKA CURRICULUM - Triani, Indri; Ghani, Alya Luthfi; Sriyandoyo, Tulus Eko; Rahmandhani, Yessi Ine; Wardhani, Aulia Kusuma (Jurnal Penelitian Pendidikan Indonesia, 2025)
The Merdeka Curriculum era demands a transformation of the education system to become more adaptive, flexible, and student-centered. Within this context, school management plays a strategic role as the main driver in improving the quality of education. This article aims to examine in depth the role of school management in supporting the implementation of the Merdeka Curriculum to create quality, relevant, and sustainable education. This study uses a qualitative approach with a library research method, where data is collected and analysis from various scientific literature sources, education policies, and relevant previous research. The findings indicate that school management plays a crucial role in the successful implementation of the Merdeka Curriculum. School management functions not only as an administrative manager but also as a learning facilitator and strategic guide for educational quality development. This research is beneficial for educators, especially school principals, to understand the strategic role of school management in improving the quality of education in the Merdeka Curriculum era.